Síntese do ácido fosfotúngstico e otimização da reação de esterificação do ácido oléico com etanol - Soares, Mário Rodrigo dos Santos (2013)
In this work the synthesis of phosphotungstic acid and optimization of esterification reaction of oleic acid with ethanol were investigated. The synthesis of the catalyst H3PW12O40 by conventional and microwave assisted methods were performed. The catalysts synthesized and a commercial were characterized by thermal analyses, XRD, FTIR, SEM and of surface area measurements, being observed characteristic properties of the H3PW12O40. The esterification reactions were performed with a commercial H3PW12O40 catalyst and also with H2SO4. The optimization of conversion in the reaction was carried out by means of two-level factorial designs. Initially, an exploratory 24 factorial design was carried out in order to identify main factors (molar ratio oleic acid:ethanol, amount of catalyst, temperature and time) affecting % conversion of ester. After that, the 24 factorial design was expanded and adjusted resulting in 25 factorials designs. In one of them, the reactions were carried out including the type of catalyst as a factor to enable a comparative evaluation of both H3PW12O40 and H2SO4. The temperature was the main factor affecting the conversion which increased 27.2 % in media when the temperature changes from 45 to 75 oC. Therefore, the temperature was fixed at 75 oC and the other 25 factorial design, including the heating source conventional or by ultrasound was performed. In this factorial design was observed that the ultrasound-assisted reactions had shown an averaged increasing of 5,5 % in the conversion. The maximum conversion was around 80 % with both of catalysts. Finally, based in the results of factorial designs, experiments with higher temperature, amount of catalyst and time were carried out and a conversion of around 90 % was achieved. The molar ratio of oleic acid:ethanol did not significantly affect the conversion in all conditions investigated. Under the optimized condition the conversion obtained in the heterogeneous reaction with H3PW12O40 was the same of the homogeneous reaction catalyzed by H2SO4. Also, it was carried out a preliminary study of recovery of the catalyst where the characterization by XRD, FTIR, thermal analyses and SEM showed that the recovered catalyst presents the same structural, spectroscopic and thermal properties than a typical of H3PW12O40. The catalyst recovered and treated at 300 °C was employed in a conventional esterification reaction and the conversion equivalent to that one with catalyst used for the first time was found.